Characterizing the determinants of sexual dissatisfaction among heterosexuals: The specific role of dyadic coping. Issue 5 (28th June 2021) - Wawrziczny, Emilie; Nandrino, Jean‐Louis; Constant, Emilie; Doba, Karyn
Abstract : Sexual satisfaction is the most frequently studied sexual component of human sexuality related to its link with relationship satisfaction and stability (S. Sprecher & R. M. Cate, 2004. The handbook of sexuality in close relationships, pp. 235–256. Mahwah, NJ: Taylor & Francis). Previous studies have shown that sexual satisfaction is affected by personal, interpersonal, social and cultural variables, but few studies have considered the associations between these variables. The aim of this study was to evaluate a complex model of sexual satisfaction considering these various levels of variables and their associations. The study was conducted online and comprised 457 individuals in the final sample. The French version of the index of sexual satisfaction evaluated the level of sexual dissatisfaction. Personal, interpersonal, social and cultural variables were assessed with questionnaires and their associations were investigated with the partial least squares‐path method. The association between dyadic coping (positive and negative) and sexual dissatisfaction was mediated by relationship satisfaction. The model also showed three sequential mediations through dyadic coping and relationship satisfaction: first between intra‐individual vulnerability and sexual dissatisfaction, second between intra‐individual resources and sexual dissatisfaction, and third between conjugal characteristics and sexual dissatisfaction. The simple and sequential mediations were stronger for positive dyadic coping. The relationship between intra‐individual resources and positive dyadic coping was significantly stronger in women, while the relationship between conjugal characteristics and positive dyadic coping was stronger in men. Dyadic coping plays a key role in sexual dissatisfaction. Clinical interventions should reinforce positive self‐image (particularly in women), support emotional and physical vulnerabilities, and promote more supportive dyadic coping (particularly in men in a long‐term relationship).